Bio-electrochemical removal of nitrate from water and wastewater-A review - Ghafari, S.; Hasan, M.; Aroua, M.K. (Elsevier, 2008)
Nitrates in different water and wastewater streams raised concerns due to severe impacts on human and animal health. Diverse methods are reported to remove nitrate from water streams which almost fail to entirely treat nitrate, except biological denitrification which is capable of reducing inorganic nitrate compounds to harmless nitrogen gas. Review of numerous studies in biological denitrification of nitrate containing water resources, aquaculture wastewaters and industrial wastewater confirmed the potential of this method and its flexibility towards the remediation of different concentrations of nitrate. The denitrifiers could be fed with organic and inorganic substrates which have different performances and subsequent advantages or disadvantages. Review of heterotrophic and autotrophic denitrifications with different food and energy sources concluded that autotrophic denitrifiers are more effective in denitrification. Autotrophs utilize carbon dioxide and hydrogen as the source of carbon substrate and electron donors, respectively. The application of this method in bio-electro reactors (BERs) has many advantages and is promising. However, this method is not so well established and documented. BERs provide proper environment for simultaneous hydrogen production on cathodes and appropriate consumption by immobilized autotrophs on these cathodes. This survey covers various designs and aspects of BERs and their performances.